Survivability of IED components, suitcases, their contents and luggage containers in suitcase bombs - Erwin Vermeij (Forensic Science International: Reports, 2024)
One of the most striking attacks on a commercial passenger airliner was the bombing of Pan Am Flight 103 (PA103) on 21 December 1988. Shortly after departure, the Boeing 747 “Clipper Maid of the Seas” broke apart over the Scottish town of Lockerbie. All 259 passengers and crew were killed, along with 11 residents of Lockerbie. The bombing of flight PA103 is still subject to controversy. The origin of a crucial piece of evidence, a fragment of circuit board, is highly questioned. One of the reasons for this ongoing controversy is probably that circumstantial evidence, that led to the conviction of a Libyan, is not supported by other evidence. Almost nothing is published in the forensic literature regarding the survivability of components that make up an improvised explosive device (IED). To gain insight into the survivability of IED components, suitcases, their contents, and luggage containers, a series of controlled experiments were carried out in which suitcase bombs, positioned in different configurations in aluminium LD3 luggage containers, were detonated. From the results, it could be seen that the major part of the suitcases, their contents and the LD3 containers survived the explosion. Also, almost all components of the IED itself survived the explosion to a greater or lesser extent.